Bulbophyllum trichocephalum (Schltr.) Tang and Wang First Report of its Occurrence from India - Shukla, B. K. (Indian Forester, 1987)
In this paper, the occurrence of Bulbophyllum trichocephalum (Schltr ) Tang and Wang is reported for the first time in India. This orchid was collected from the Namdapha Biosphere Reserve in Tirap (Arunachal Pradesh).